Advances in Biomaterial Coatings for Biomedical Implants: Engineering Approaches and Surface Modification Techniques - Jadhav, Dhiraj Rajendra; G. Damle, Prajitsen (Journal of Neonatal Surgery, 2025)
This review paper delves into the pivotal role of engineering in advancing biomaterials for biomedical applications, with a specific focus on coatings and surface modifications for implants. Through a comprehensive analysis of various mechanical tests, morphological evaluations, and in-vitro assessments, researchers have significantly enhanced the properties of biomaterial coatings, leading to improved biocompatibility, wear resistance, and overall performance of biomedical implants. The document underscores the importance of specific base materials and coating methods, such as SS316L, TiAl Alloy/Ti alloy, thermal spraying, physical vapor deposition, and plasma nitriding, in the realm of biomaterial engineering. Insights provided in this review shed light on the innovative techniques, tests, and materials utilized in the development and evaluation of biomaterial coatings, contributing to the continuous improvement and advancement of biomedical implants in the healthcare industry.